Progressive pseudorheumatoid dysplasia involving a novel CCN6 mutation: a case report - Li, Yu; Huang, Zhengping; Yan, Yun; Guo, Feng; Wei, Gang; Wang, Yue; Xie, Yu (Frontiers in Immunology, 2024)
Objective This study aims to report a case of progressive pseudorheumatoid dysplasia (PPRD) with two kinds of cellular communication network factor 6 (CCN6) gene mutation. In this paper, the clinical profile and the process of diagnosis were analyzed, and the related literature was reviewed. A 15-year-old boy, who developed progressive ankle and hip joint pain and enlargement with spine involvement, was diagnosed with PPRD. The erythrocyte sedimentation rate and C-reactive protein (CRP) were in the normal range; rheumatoid factor and anti-cyclic citrullinated peptide antibody (ACPA) were all negative. Human leukocyte antigen 27 (HLA-B27) was also negative. Cene study discovered two kinds of mutations in CCN6 gene: c. 802T>C and c.624dup. Radiographic studies revealed spine platyspondyly and shaped beaked, osteoporosis, and bilateral symmetric bony enlargements of the interphalangeal joints. Hip shows bilateral acetabulum and femoral head bone marrow edema, which revealed hip arthritis. Gene detection, laboratory examination, and typical radiographic features are helpful for the diagnosis of PPRD. This is the first report of c. 802T>C and c.624dup mutations in patients with PPRD in our country.